2017
DOI: 10.1016/j.redox.2017.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-meditated pathways of organ failure upon inflammation

Abstract: Liver failure induced by systemic inflammatory response (SIRS) is often associated with mitochondrial dysfunction but the mechanism linking SIRS and mitochondria-mediated liver failure is still a matter of discussion. Current hypotheses suggest that causative events could be a drop in ATP synthesis, opening of mitochondrial permeability transition pore, specific changes in mitochondrial morphology, impaired Ca2+ uptake, generation of mitochondrial reactive oxygen species (mtROS), turnover of mitochondria and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 158 publications
(166 reference statements)
0
82
0
Order By: Relevance
“…Over the past decades, mitochondria have been well recognized as major regulators that control heart function and cardiomyocyte viability under physiological and pathological conditions. 4,5 Structurally, mitochondrial homeostasis is closely regulated by mitochondrial dynamics, including mitochondrial fission, mitochondrial fusion, and mitophagy. 6,7 Ample evidence has indicated that I/R injury primarily involves multiple factors that converge on provoking the onset of mitochondrial fission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decades, mitochondria have been well recognized as major regulators that control heart function and cardiomyocyte viability under physiological and pathological conditions. 4,5 Structurally, mitochondrial homeostasis is closely regulated by mitochondrial dynamics, including mitochondrial fission, mitochondrial fusion, and mitophagy. 6,7 Ample evidence has indicated that I/R injury primarily involves multiple factors that converge on provoking the onset of mitochondrial fission.…”
Section: Introductionmentioning
confidence: 99%
“…7 In the failing heart, the overexpression of OPA1 reverses mitochondrial function and improves cardiac performance. 31 Mechanistically, OPA1 expression is potentially regulated by the AMPK pathway, 5 which is also reported to be associated with mitophagy modification. Along with the well-documented role played by OPA1-related mitochondrial fusion and mitophagy in cardioprotection, it is very worthwhile to explore whether melatonin protects the reperfused heart by activating OPA1-related mitochondrial fusion and mitophagy in a manner dependent on the AMPK signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that LPS increases NADPH oxidase expression and activation in different tissues and that the boost of ROS production by LPS is largely dependent on NADPH oxidase activity . ROS modulates a variety of physiopathological effects, such as the production of pro‐inflammatory cytokines, which is a hallmark of endotoxaemia and multiorgan dysfunction . c‐Src and PI3K are important enzymes involved in the modulation of NADPH oxidase activity mainly through p47 phox phosphorylation .…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia is also a hallmark of endotoxemia, and has been associated with a worse clinical outcome as evidenced by elevated risk of bleeding, many times resulting in death . Overproduction of reactive oxygen species (ROS) by LPS is detrimental to the normal functioning of organs, thus contributing to multiorgan failure …”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are important organelle in cells, which perform many roles beyond energy production, including the generation of ROS, redox molecules and metabolites, regulation of cell signaling and cell death, and biosynthetic metabolism. 21,22 Therefore, it is not surprising mitochondria dysfunction is an important inducing factor of many diseases. 23 Oxidative stress plays a critical role in the mitochondria dysfunction.…”
Section: Introductionmentioning
confidence: 99%